2006
DOI: 10.1111/j.1348-0421.2006.tb03780.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mouse Model for MPO‐ANCA‐Associated Glomerulonephritis

Abstract: It has been shown that myeloperoxidase (MPO) and the MPO-specific anti-neutrophil cytoplasmic auto-antibody (MPO-ANCA) are risk factors for the development of glomerulonephritis (GN). High titers of MPO-ANCA are frequently detected (2,4,5,8) in the sera of patients with microscopic polyangiitis (MPA) or crescentic GN (CrGN). Animal models have been used for understanding the mechanisms for the development of vasculitis, as a basis for establishing new therapeutic strategies. The SCG/Kj mouse is a model of spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The model which we performed was a classical immunecomplex-mediated glomerulonephritis rather than AAV models, but the generation of MPO-ANCA and neutrophil-mediated glomerular inflammation in this model have been demonstrated. 28 Our in vivo findings support that the loss of membrane-bound SEMA4D is crucially involved in the development of neutrophil-mediated vascular inflammation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The model which we performed was a classical immunecomplex-mediated glomerulonephritis rather than AAV models, but the generation of MPO-ANCA and neutrophil-mediated glomerular inflammation in this model have been demonstrated. 28 Our in vivo findings support that the loss of membrane-bound SEMA4D is crucially involved in the development of neutrophil-mediated vascular inflammation.…”
Section: Discussionsupporting
confidence: 76%
“… 13 26 27 Consistent with this, we confirmed that soluble SEMA4D promoted the permeability (see online supplementary figure S3A ) and interleukin (IL)-8 secretion of endothelial cells (see online supplementary figure S3B ), without affecting the expression of endothelial adhesion molecules (see online supplementary figure S3C ). To further assess the significance of SEMA4D in AAV pathogenesis, we next studied an in vivo neutrophil-mediated vasculitis model, 28 using wild-type (WT) and SEMA4D-deficient ( SEMA4D −/− ) mice. Contrary to expectations, SEMA4D −/− mice exhibited enhanced phenotypes in comparison with WT mice (see online supplementary figure S4A-E ).…”
Section: Resultsmentioning
confidence: 99%
“…In 10 patients (37%), pulmonary lesions appeared first, in 11 patients (40.7%) the lesions developed simultaneously, and in only 5 patients (8.5%) did the renal lesions appear first. Yumura et al [30] have reported that histological features of lung damage appeared before glomerular changes in a mouse model for MPO-ANCA-associated glomerulonephritis. This suggests the possibility that some kinds of lung damage precede the onset of renal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these assessments are complicated by WT mice developing injurious autoimmune responses to mMPO, which would not be expected to occur in MPO Ϫ/Ϫ mice (because of genetic deletion of the potential endogenous autoantigen). Some patients with anti-GBM GN develop circulating autoantibodies (ANCA) against MPO (41), and several murine models of MPO-ANCA-associated crescentic GN have been recently described (21,36,42,43 Humoral responses to sheep globulin were also enhanced in the absence of MPO. Consistent with the cytokine data, the IgG3:IgG1 (Th1:Th2) ratio was enhanced in MPO Ϫ/Ϫ mice.…”
Section: Glomerular Neutrophil Accumulation Was Assessed In Wt and Mpomentioning
confidence: 99%